Epoxy asphalt concrete for heavy traffic and method for producing the same
Patent Information
- Application Number
- CN202611243020.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-17
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]本发明旨在解决现有环氧沥青混凝土在重载交通下无法同时满足高强度、高韧性及界面长效粘结的技术难题,提供一种通过构建“分子级-微米级-宏观级”多尺度梯度互穿网络结构的环氧沥青混凝土
1、构建梯度互穿网络结构,通过反应性相容剂和分步原位聚合,实现分子链缠结到三维交联的梯度过渡,解决刚-韧矛盾;骨料和纤维表面均通过氨基与环氧基共价连接,提升界面粘结强度;“点-线-网”多级增强:纳米粒子(点)、接枝纤维(线)、互穿网络(网)形成多级应力传递系统,疲劳寿命提升50%以上;工艺协同:三步法每一步都为下一步预留活性位点,最终形成整体化学交联网络。
Smart Images

Figure CN122958103A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of asphalt concrete preparation technology, specifically relating to an epoxy asphalt concrete for heavy-duty traffic and its preparation method. Background Technology
[0002] Heavy traffic refers to road conditions characterized by frequent passage of large-tonnage trucks, container trucks, mining trucks, and other vehicles with high axle loads, wheel pressures, and traffic volumes. Under such traffic conditions, ordinary asphalt concrete is highly susceptible to early-stage defects such as rutting, shoving, cracking, and bulging due to insufficient binder strength and high temperature sensitivity, which seriously affects the service life of the pavement and driving safety.
[0003] Epoxy asphalt concrete is a high-performance pavement material made by using epoxy resin and curing agent as modifiers or main binders, which are cross-linked and cured with petroleum asphalt in a certain proportion to form an irreversible thermosetting three-dimensional network structure. Epoxy asphalt concrete has advantages such as high strength, high modulus, strong resistance to permanent deformation, fatigue resistance, and corrosion resistance, and is especially suitable for heavy traffic sections.
[0004] However, current epoxy systems exhibit high brittleness after curing, making them prone to shrinkage cracks in low-temperature seasons or regions with large temperature differences. This can lead to reflective cracking or water damage. While adding flexible materials can partially mitigate these issues, it often comes at the cost of sacrificing rutting resistance. Furthermore, existing epoxy asphalt concrete experiences a sharp decline in fatigue life when axle loads increase further (e.g., exceeding 13t single axle load) or when overloading occurs frequently, making it susceptible to brittle fracture failure rather than the plastic deformation failure of traditional asphalt pavements. In addition, the design and evaluation of most epoxy asphalt mixtures still rely on indicators for ordinary or modified asphalt (such as dynamic stability and freeze-thaw splitting strength ratio), which fail to accurately reflect the damage evolution under heavy, low-speed, and high-frequency loads, resulting in a disconnect between material design and service performance.
[0005] The core issue causing failure under heavy loads is not insufficient material strength, but rather the interfacial delamination between epoxy resin and asphalt, and the debonding between organic binders and inorganic aggregates. Current technologies lack effective chemical bonding designs for these two interfaces. Summary of the Invention
[0006] This invention aims to solve the technical problem that existing epoxy asphalt concrete cannot simultaneously meet the requirements of high strength, high toughness, and long-term interfacial bonding under heavy traffic conditions. It provides an epoxy asphalt concrete that constructs a multi-scale gradient interpenetrating network structure at the molecular, micron, and macro scales.
[0007] To achieve the above objectives, the present invention provides the following technical solution: This invention discloses an epoxy asphalt concrete for heavy-duty traffic, wherein the epoxy asphalt concrete is composed of binder and aggregate; and the mass ratio of binder to aggregate is 5.5~6.5%.
[0008] The binder is composed of modified epoxy resin, environmentally friendly curing agent, long-chain primary amine curing agent, matrix asphalt, and reactive compatibilizer; wherein the modified epoxy resin is 12-20 parts, the environmentally friendly curing agent is 3-5 parts, the long-chain primary amine curing agent is 5-13 parts, the matrix asphalt is 30-80 parts, and the reactive compatibilizer is 2-3 parts. The aggregate consists of coarse aggregate, fine aggregate, mineral powder, and filler, wherein the mass ratio of coarse aggregate: fine aggregate: mineral powder: filler is 60-70:15-25:5-15:0.5-1.
[0009] Furthermore, the modified epoxy resin is HTBN-modified E-51 epoxy resin, the environmentally friendly curing agent is bio-based polyetheramine curing agent, the long-chain primary amine curing agent is oleylamine curing agent, and the base asphalt is 70# road petroleum asphalt. The modified epoxy resin is prepared by mixing HTBN and E-51 epoxy resin at a mass ratio of 10-30:100, adding 0.1-0.5% triphenylphosphine, heating to 120-150℃ under nitrogen protection, stirring and reacting for 2-4 hours, and utilizing the ring-opening addition reaction between the terminal hydroxyl groups of HTBN and the epoxy groups to obtain the modified epoxy resin. The preparation method of the environmentally friendly curing agent is as follows: using bio-based 1,3-propanediol as a starting agent, it is ring-opened polymerized with propylene oxide under the action of an alkaline catalyst to obtain a bio-based polyether polyol; then the bio-based polyether polyol is mixed with liquid ammonia and subjected to a hydroammoniation reaction in the presence of hydrogen atmosphere and nickel-based catalyst, with the reaction temperature controlled at 130~280℃ and the pressure at 3~15MPa. After the reaction is completed, the product is deammonerated, dehydrated, and filtered to obtain the bio-based polyether amine. The reactive compatibilizer is a maleic anhydride-terminated polyethylene glycol-epoxy resin block copolymer. One end of the anhydride group reacts with the epoxy resin, while the other end of the anhydride group forms chemical bonds or strong hydrogen bonds with the polar components in the asphalt. At the same time, the polyethylene glycol segments are compatible with the asphalt and act as molecular bridges between the two phases.
[0010] Furthermore, the coarse aggregate is basalt crushed stone, including aggregates of three sizes: 3-5mm, 5-10mm, and 10-15mm; the fine aggregate is 0-3mm limestone aggregate; the mineral powder is limestone mineral powder; and the filler is composed of nano-SiO2 / CaCO3, KH-550 grafted short-cut basalt fiber, and anti-aging agent in a mass ratio of 5~10:2~4:0.5~1.0.
[0011] Furthermore, the particle size of the SiO2 / CaCO3 is 20-80 nm; the anti-aging agent is any one of antioxidant 1010, antioxidant 1076, and antioxidant 2246.
[0012] Furthermore, the preparation method of epoxy asphalt concrete for heavy-duty traffic includes the following steps: S1. Heat the base asphalt to 130-150℃ and add a reactive compatibilizer. Shear at high speed of 2000-3000 rpm for 10-30 min to obtain active asphalt component A. S2. Heat the modified epoxy resin to 60-70℃, add bio-based polyetheramine curing agent, and pre-react for 10-15 minutes to obtain active epoxy component B. S3. Keep the temperature of active asphalt component A at 130-150℃ and slowly add component B while stirring vigorously. At the same time, add long-chain primary amine curing agent and continue stirring for 5-15 minutes to allow the epoxy phase to polymerize and crosslink in situ in the asphalt phase, forming an epoxy asphalt binder with an interpenetrating network structure. S4. The basalt coarse aggregate is dried at 110-120℃, sprayed with an ethanol / water solution containing γ-aminopropyltriethoxysilane, wherein the volume ratio of the ethanol / water solution is 95:5, and cured at 105-110℃ for 1-2 hours to obtain surface-aminated active aggregate; the fine aggregate and mineral powder are dried for later use; the coarse aggregate, fine aggregate, mineral powder and filler are mixed evenly to obtain component C. S5: Preheat component C to 120-170℃, add epoxy asphalt binder in proportion, mix evenly, vibrate and compact at 120-170℃, and then cure at 60℃ for 48 hours to obtain the finished product.
[0013] Furthermore, in step S5, the mixture can be directly spread and compacted during road construction, with the temperature controlled at 110-150℃. After compaction, it can be opened to traffic after one day of normal temperature curing.
[0014] The beneficial effects of this invention are as follows: 1. Constructing a gradient interpenetrating network structure, through reactive compatibilizers and stepwise in-situ polymerization, achieves a gradient transition from molecular chain entanglement to three-dimensional cross-linking, resolving the rigidity-toughness contradiction; both aggregate and fiber surfaces are covalently linked by amino and epoxy groups, improving interfacial bonding strength; "point-line-network" multi-level reinforcement: nanoparticles (points), grafted fibers (lines), and interpenetrating networks (networks) form a multi-level stress transmission system, improving fatigue life by more than 50%; process synergy: each step of the three-step method reserves active sites for the next step, ultimately forming an overall chemical cross-linked network.
[0015] 2. The epoxy asphalt concrete for heavy-duty traffic prepared by this invention solves the problems of high brittleness and easy cracking at low temperatures of traditional epoxy asphalt concrete, and is suitable for different regional climates; the curing agent used has no toxic or harmful emissions; the preparation process does not require special equipment, the construction process is similar to that of conventional asphalt concrete, and it can be directly adapted to existing road construction equipment, reducing construction costs.
[0016] 3. The raw materials selected in this invention are all conventional industrial raw materials. The core raw materials can be prepared by existing processes without the need for new equipment. The overall cost is reduced by 15%-20% compared with existing high-end heavy-duty epoxy asphalt concrete, and it has industrial promotion value.
[0017] Other advantages, objectives, and features of the invention will be set forth in the following description and will be apparent to those skilled in the art in some respects, or may be learned by practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0018] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the following figures are provided for illustration: Figure 1 This is a schematic diagram of the preparation process of the present invention. Detailed Implementation
[0019] like Figure 1 As shown, this invention discloses an epoxy asphalt concrete for heavy-duty traffic and its preparation method.
[0020] Example 1 S1. Heat 60 parts of 70# road petroleum asphalt to 140℃ and add 2.5 parts of reactive compatibilizer. Shear at 2500rpm for 20min to obtain active asphalt component A. S2. Heat 15 parts of modified epoxy resin to 65°C, add 4 parts of bio-based polyetheramine curing agent, and pre-react for 12.5 min to obtain active epoxy component B. S3. Keep the temperature of active asphalt component A at 140℃ and slowly add active epoxy component B while stirring vigorously. At the same time, add 8 parts of oleylamine curing agent. Continue stirring for 10 minutes to allow the epoxy phase to polymerize and crosslink in situ in the asphalt phase, forming an epoxy asphalt binder with an interpenetrating network structure. S4. After drying 65 parts of basalt crushed stone at 115℃, spray 1.5 parts of an ethanol / water solution containing γ-aminopropyltriethoxysilane (KH-550) onto its surface and cure it at 110℃ for 1.5h to obtain surface-aminated active aggregate; mix the active aggregate with 20 parts of pre-dried fine aggregate, 10 parts of mineral powder, 0.75 parts of filler (the mass ratio of nano-SiO2 / CaCO3, KH-550 grafted short-cut basalt fiber, and anti-aging agent is 7.5:3:0.75) evenly to obtain component C; S5: Preheat component C to 145℃, add epoxy asphalt binder at an asphalt-aggregate ratio of 6.0%, mix evenly, vibrate and compact at 140℃, and then cure at 60℃ for 48 hours to obtain the finished product.
[0021] Example 2 In Example 2, 18 parts of modified epoxy resin, 3 parts of bio-based polyetheramine curing agent, 80 parts of matrix asphalt, 3 parts of reactive compatibilizer, and 5 parts of oleylamine curing agent were used. The coarse aggregate consists of 60 parts, the fine aggregate consists of 15 parts, the mineral powder consists of 5 parts, and the filler (nano SiO2 / CaCO3, KH-550 grafted short-cut basalt fiber, and anti-aging agent in a mass ratio of 5:2:0.5) consists of 0.5 parts; epoxy asphalt binder is added at an asphalt-aggregate ratio of 6.4%.
[0022] The difference between Example 2 and Example 1 lies in the different raw material components and the different oil-aggregate ratio, but both are within the protection scope of this invention, and the epoxy asphalt concrete prepared is also suitable for construction site applications.
[0023] Example 3 In Example 3, 12 parts of modified epoxy resin, 5 parts of bio-based polyetheramine curing agent, 40 parts of matrix asphalt, 2 parts of reactive compatibilizer, and 13 parts of oleylamine curing agent were used. The composition consists of 70 parts coarse aggregate, 25 parts fine aggregate, 15 parts mineral powder, and 1 part filler (nano SiO2 / CaCO3, KH-550 grafted short-cut basalt fiber, and anti-aging agent in a mass ratio of 10:4:1.0); epoxy asphalt binder is added at an asphalt-aggregate ratio of 5.6%.
[0024] The difference between Example 3 and Example 1 lies in the different raw material components and the different oil-aggregate ratio, but both are within the protection scope of this invention, and the epoxy asphalt concrete prepared is also suitable for construction site applications.
[0025] principle: 1. In this invention, E-51 epoxy resin modified with hydroxyl-terminated liquid nitrile butadiene rubber (HTBN) and bio-based polyetheramine curing agent and oleylamine curing agent, in the presence of a reactive compatibilizer, undergoes chemical cross-linking and physical entanglement with the asphaltenes molecular chains of the matrix asphalt, forming an IPN structure in which the epoxy phase and the asphalt phase are interpenetrating and inseparable; in addition, the reactive compatibilizer is a maleic anhydride-terminated polyethylene glycol-epoxy resin block copolymer, one end of which undergoes esterification reaction with the terminal hydroxyl groups of HTBN, and the other end of which forms chemical bonds or strong hydrogen bonds with polar components (such as hydroxyl and amine groups) in the asphalt. At the same time, the polyethylene glycol segments are compatible with the asphalt, thus acting as a "molecular bridge" between the two phases.
[0026] 2. In this invention, the short-cut basalt fibers grafted onto the surface of the silane coupling agent KH-550 (γ-aminopropyltriethoxysilane) are combined with nano-SiO2 / CaCO3 composite fillers. The surface of the short-cut basalt fibers is grafted with primary amino groups (-NH2) through KH-550. These amino groups can undergo ring-opening addition reactions with the epoxy groups in the epoxy asphalt binder to form strong chemical bonds, enabling the fibers to be covalently connected to the epoxy asphalt matrix. The nano-composite fillers are uniformly dispersed in the epoxy phase through in-situ polymerization, forming a "point-line" synergistic reinforcing network with the fibers.
[0027] To verify the superiority of the present invention, comparative examples 1-2 are provided here: Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: No reactive compatibilizer is added in step S1; the composition of the remaining raw materials and the preparation process parameters are the same as in Example 1.
[0028] This comparative example is used to examine the effect of reactive compatibilizers on the performance of the mixture.
[0029] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is as follows: In step S4, no ethanol / water solution containing γ-aminopropyltriethoxysilane (KH-550) is sprayed, and in step S3, short-cut basalt fibers without KH-550 grafting are used; the remaining raw material composition and preparation process parameters are the same as in Example 1.
[0030] This comparative example is used to investigate the effect of interfacial coupling modification on the performance of the mixture.
[0031] The performance of epoxy asphalt concrete prepared in Examples 1-3 and Comparative Examples 1-2 was tested, and the test results are shown in Table 1.
[0032] Table 1 Performance Test Results As shown in Table 1, the epoxy asphalt concrete prepared by Examples 1-3 of this invention exhibits excellent performance in terms of low-temperature flexural failure strain, freeze-thaw splitting strength ratio, residual stability, and fatigue life. In contrast, the products obtained by Comparative Examples 1-2 do not perform as well as those of Examples 1-3.
[0033] Finally, it should be noted that the above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made to it in form and detail without departing from the scope defined by the claims of the present invention.
Claims
1. An epoxy asphalt concrete for heavy-duty traffic, characterized in that: The epoxy asphalt concrete is composed of binder and aggregate; and the binder accounts for 5.5-6.5% of the aggregate by mass. The binder is composed of modified epoxy resin, environmentally friendly curing agent, long-chain primary amine curing agent, matrix asphalt, and reactive compatibilizer; wherein the modified epoxy resin is 12-20 parts, the environmentally friendly curing agent is 3-5 parts, the long-chain primary amine curing agent is 5-13 parts, the matrix asphalt is 30-80 parts, and the reactive compatibilizer is 2-3 parts. The aggregate consists of coarse aggregate, fine aggregate, mineral powder, and filler. Coarse aggregate: The mass ratio of fine aggregate: mineral powder: filler is 60-70:15-25:5-15:0.5-1.
2. The epoxy asphalt concrete for heavy-duty traffic according to claim 1, characterized in that: The modified epoxy resin is HTBN-modified E-51 epoxy resin, the environmentally friendly curing agent is bio-based polyetheramine curing agent, the long-chain primary amine curing agent is oleylamine curing agent, and the base asphalt is 70# road petroleum asphalt. The modified epoxy resin is prepared by mixing HTBN and E-51 epoxy resin at a mass ratio of 10-30:100, adding 0.1-0.5% triphenylphosphine, heating to 120-150℃ under nitrogen protection, stirring and reacting for 2-4 hours, and utilizing the ring-opening addition reaction between the terminal hydroxyl groups of HTBN and the epoxy groups to obtain the modified epoxy resin. The preparation method of the environmentally friendly curing agent is as follows: using bio-based 1,3-propanediol as a starting agent, it is ring-opened polymerized with propylene oxide under the action of an alkaline catalyst to obtain a bio-based polyether polyol; then the bio-based polyether polyol is mixed with liquid ammonia and subjected to a hydroammoniation reaction in the presence of hydrogen atmosphere and nickel-based catalyst, with the reaction temperature controlled at 130~280℃ and the pressure at 3~15MPa. After the reaction is completed, the product is deammonerated, dehydrated, and filtered to obtain the bio-based polyether amine curing agent. The reactive compatibilizer is a maleic anhydride-terminated polyethylene glycol-epoxy resin block copolymer. One end of the anhydride group reacts with the epoxy resin, while the other end of the anhydride group forms chemical bonds or strong hydrogen bonds with the polar components in the asphalt. At the same time, the polyethylene glycol segments are compatible with the asphalt and act as molecular bridges between the two phases.
3. The epoxy asphalt concrete for heavy-duty traffic according to claim 2, characterized in that: The coarse aggregate is basalt crushed stone, including three sizes: 3-5mm, 5-10mm, and 10-15mm; the fine aggregate is 0-3mm limestone aggregate; the mineral powder is limestone mineral powder; the filler is composed of nano-SiO2 / CaCO3, KH-550 grafted short-cut basalt fiber, and anti-aging agent in a mass ratio of 5~10:2~4:0.5~1.
0. It is a composite of nano-SiO2 / CaCO3, KH-550 grafted short-cut basalt fiber, and anti-aging agent.
4. An epoxy asphalt concrete for heavy-duty traffic according to claim 3, characterized in that: The particle size of the SiO2 / CaCO3 is 20-80 nm; the anti-aging agent is any one of antioxidant 1010, antioxidant 1076, and antioxidant 2246.
5. A method for preparing epoxy asphalt concrete for heavy-duty traffic as described in any one of claims 1-4, characterized in that: Includes the following steps, S1. Heat the base asphalt to 130-150℃ and add a reactive compatibilizer. Shear at high speed of 2000-3000 rpm for 10-30 min to obtain active asphalt component A. S2. Heat the modified epoxy resin to 60-70℃, add the bio-based polyetheramine curing agent, and pre-react for 10-15 minutes to obtain the active epoxy component B. S3. Keep the temperature of active asphalt component A at 130-150℃ and slowly add component B while stirring vigorously. At the same time, add long-chain primary amine curing agent and continue stirring for 5-15 minutes to allow the epoxy phase to polymerize and crosslink in situ in the asphalt phase, forming an epoxy asphalt binder with an interpenetrating network structure. S4. The basalt coarse aggregate is dried at 110-120℃, sprayed with an ethanol / water solution containing γ-aminopropyltriethoxysilane, wherein the volume ratio of the ethanol / water solution is 95:5, and cured at 105-110℃ for 1-2 hours to obtain surface-aminated active aggregate; the fine aggregate and mineral powder are dried for later use; the coarse aggregate, fine aggregate, mineral powder and filler are mixed evenly to obtain component C. S5: Preheat component C to 120-170℃, add epoxy asphalt binder in proportion, mix evenly, vibrate and compact at 120-170℃, and then cure at 60℃ for 48 hours to obtain the finished product.
6. The method for preparing epoxy asphalt concrete for heavy-duty traffic according to claim 5, characterized in that: In step S5, the mixture can be directly spread and compacted during road construction, with the temperature controlled at 110-150℃. After compaction, it can be opened to traffic after one day of normal temperature curing.